2002
DOI: 10.1209/epl/i2002-00579-4
|View full text |Cite
|
Sign up to set email alerts
|

Semicausal operations are semilocalizable

Abstract: We prove a conjecture by DiVincenzo, which in the terminology of Preskill et al. [quant-ph/0102043] states that "semicausal operations are semilocalizable". That is, we show that any operation on the combined system of Alice and Bob, which does not allow Bob to send messages to Alice, can be represented as an operation by Alice, transmitting a quantum particle to Bob, and a local operation by Bob. The proof is based on the uniqueness of the Stinespring representation for a completely positive map. We sketch s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
126
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 15 publications
(23 reference statements)
1
126
0
Order By: Relevance
“…Since the maps ρ → I ⊗ ρ, S * and I ⊗ σ → σ are all CP, we have σ = N * (ρ), where N * is a CP trace preserving map from states on K in to states on H in . Remarkably, the same mathematical structure of Lemma 2 characterizes semi-causal quantum operations [7], i.e. operations on bipartite systems that allow signaling from system A to system B but not viceversa.…”
Section: Proofmentioning
confidence: 92%
“…Since the maps ρ → I ⊗ ρ, S * and I ⊗ σ → σ are all CP, we have σ = N * (ρ), where N * is a CP trace preserving map from states on K in to states on H in . Remarkably, the same mathematical structure of Lemma 2 characterizes semi-causal quantum operations [7], i.e. operations on bipartite systems that allow signaling from system A to system B but not viceversa.…”
Section: Proofmentioning
confidence: 92%
“…[58] Beckman, Gottesmann, Nielsen, and Preskill introduced the notions of semicausal and semilocalizable quantum channel for the purpose of studying the constraints on quantum dynamics of bipartite systems imposed by relativistic causality. Subsequently, Eggeling, Schlingemann, and Werner [59] proved the equivalence between semicausality and semilocalizability (see also Ref. [60] for an extensive discussion on the topic).…”
Section: Causally Ordered Channels and Channels With Memorymentioning
confidence: 99%
“…It is easily proved that localizable operators are causal. It was shown that semicausal operators are always semilocalizable (Eggeling, Schlingemann, and Werner, 2002). However, there are causal operations that are not localizable (Beckman et al, 2001).…”
Section: E the No-communication Theoremmentioning
confidence: 99%